The role of Iyengar Yoga practice in chronic, non-malignant pain. A clinical review focused on current evidence - Chrysanthi Batistaki*, Georgios Batistakis, Katerina Pylava, Paraskevi Matsota (Innovative Journal of Medical and Health Sciences, 2020)
Background: Chronic pain leads to severe functional disability and worsening of quality of life. The aim of this review is to assess the efficacy of Iyengar yoga on chronic non-malignant pain, in terms of pain intensity, functional status, and quality of life. Methods: Research focused on the efficacy of Iyengar yoga on non-malignant chronic pain, from 2019 and back, with studies only in English language. Results: Studies about Iyengar yoga were limited (N=17). Six studies were identified on low back pain, 3 on chronic neck pain, 2 on osteoarthritis, 2 on rheumatoid arthritis, 1 on irritable bowel syndrome and 1 on multiple sclerosis. Results were positive for low back pain, and beneficial in all other entities. Furthermore, Iyengar yoga requires an experienced certified teacher, and regular home practice. Conclusions: Iyengar yoga with could be beneficial as an adjuvant for chronic pain diseases, especially in patients with low back pain. Key words: Yoga–Iyengar–pain–chronic